Inhibition of Filiform Corrosion on Organic-Coated Magnesium-Containing Galvanized Steel by Smart-Release Ion Exchange Pigments - Hamilton McMurray (ECS Transactions, 2017)
This paper describes a systematic kinetic study on the inhibitory effect of anion exchange Hydrotalcite-based pigments on filiform corroding hot dipped Zn-(1-2 w%)Mg-(1-2 w%)Al galvanized steel. Filiform corrosion was initiated via scribing the organic-coated samples and introducing a corrosive electrolyte in the defect. Following filiform corrosion initiation, the time-dependent extent of coating delamination was determined photographically over a period of six weeks. It is positively demonstrated that the addition of smart-release pigments in the organic coating greatly suppresses the rate of filiform corrosion. The inhibitor efficiency is shown to increase in the order: carbonate < benzotriazole < benzotriazolate. The release of carbonates leads to filiform corrosion increase.